2019
DOI: 10.3390/nu11051016
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D: Is It Time to Consider the Use of Calcifediol?

Abstract: Hypovitaminosis D is becoming a notable health problem worldwide. A consensus exists among several different medical societies as to the need for adequate levels of vitamin D for bone and general health. The correct method by which to restore normal vitamin D levels is still a matter of debate. Although cholecalciferol remains the most commonly distributed form of vitamin D supplementation worldwide, several drugs with vitamin D activity are available for clinical use, and making the correct selection for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 117 publications
3
42
0
5
Order By: Relevance
“…Our results indicate that the potency of 25(OH)D 3 in the HyD ® supplement was more than five times that of D3 for the dietary matrix studied. A greater potency of 25(OH)D 3 relative to D3 for raising plasma 25(OH)D 3 concentration is consistent with prior work in dogs and dosage trials in other species ( 17 , 32 , 43 , 45 , 46 ) .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results indicate that the potency of 25(OH)D 3 in the HyD ® supplement was more than five times that of D3 for the dietary matrix studied. A greater potency of 25(OH)D 3 relative to D3 for raising plasma 25(OH)D 3 concentration is consistent with prior work in dogs and dosage trials in other species ( 17 , 32 , 43 , 45 , 46 ) .…”
Section: Discussionsupporting
confidence: 87%
“…Comparatively, alimentary uptake of 25(OH)D 3 is more rapid than that of D3 because it has greater water solubility and intestinal protein-binding capabilities ( 30 , 31 ) . Alimentary 25(OH)D 3 enters circulation more directly relative to D3, first in portal blood then systemic circulation bound to plasma proteins ( 32 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Several factors affect vitamin D status, such as sun exposure, skin pigmentation (less pigment allowing to synthesize more previtamin D), time of day, season, area of skin exposed to sunlight, body weight (only 1% of body fat increase was associated with 0.46 ± 0.22 ng/mL reduction in circulating 25(OH)D [51]), latitude, food-related vitamin D intake, and age (older people synthesizing less previtamin D) [48, 52]. Recommended daily intake and tolerable upper intake of vitamin D for adults are 600 IU/day and 4,000 IU/day, respectively [53].…”
Section: Vitamin D Deficiency and Insufficiencymentioning
confidence: 99%
“…PPIs, enhancing gastric pH, could interfere with calcium absorption. It can lead to a negative calcium balance with consequent secondary hyperparathyroidism and increased bone loss [ 5 , 16 , 17 ]. Chonan et al in an animal in vivo evaluation showed that rats on omeprazole therapy presented calcium malabsorption, and the reduction of intestinal pH with dietary lactate prevented the calcium absorption in rats fed with omeprazole [ 18 ].…”
Section: Potential Mechanisms Of Ppis Induced Fracture Riskmentioning
confidence: 99%